2023
DOI: 10.38007/ijhpm.2023.040116
|View full text |Cite
|
Sign up to set email alerts
|

Rhein Improves Sepsis Rats by Reducing Inflammatory Reaction and Regulating AQP2 Acute Renal Injury

Abstract: Background: Inflammation is a typical manifestation of sepsis related acute renal injury. AQP2 is considered to play an important role in renal fluid transport. This study aims to explore whether rhein has a protective effect on renal injury and its potential mechanism. Methods: A sepsis rat model of acute renal injury was established. 60 SD rats were randomly divided into control group, model group, high rhein (200mg/kg), medium rhein (100mg/kg), low dose rhein (50mg/kg) and dexamethasone group. Observe the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Interestingly, in rats exposed to LPS, treatment with dexpanthenol increased AQP2 mRNA expression in kidney tissues through the silent information regulator 1 (SIRT1) signaling pathway [ 43 ]. Liu et al demonstrated that the downregulation of AQP2 protein expression in rats with LPS-induced kidney injury could be attenuated by rhein treatment, an anthraquinone utilized in Chinese medicine with anti-inflammatory, antioxidant, and hepatoprotective properties [ 42 , 80 ]. Pre-treatment with propofol has been demonstrated to protect LPS-exposed rats with sepsis-induced kidney injury from further renal complications by preventing the downregulation of AQP2 expression [ 44 ].…”
Section: Aquaporin Regulators In Experimental Models Of Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in rats exposed to LPS, treatment with dexpanthenol increased AQP2 mRNA expression in kidney tissues through the silent information regulator 1 (SIRT1) signaling pathway [ 43 ]. Liu et al demonstrated that the downregulation of AQP2 protein expression in rats with LPS-induced kidney injury could be attenuated by rhein treatment, an anthraquinone utilized in Chinese medicine with anti-inflammatory, antioxidant, and hepatoprotective properties [ 42 , 80 ]. Pre-treatment with propofol has been demonstrated to protect LPS-exposed rats with sepsis-induced kidney injury from further renal complications by preventing the downregulation of AQP2 expression [ 44 ].…”
Section: Aquaporin Regulators In Experimental Models Of Sepsismentioning
confidence: 99%
“…Table 3 lists the regulators of AQP expression and their effects on experimental sepsis progression. LPS-exposed rats Pre-treatment with increasing concentrations of soy isoflavone resulted in dose-dependent upregulation of AQP1 mRNA and protein, alleviating pulmonary edema and lung damage [37] LPS-exposed rats Hydrogen-rich saline reverses AQP1 mRNA and protein downregulation [38] LPS-exposed rats Selenium treatment resulted in the upregulation of AQP1 protein expression in the kidneys [39] CLP rats MEF2C treatment attenuated the progress of lung injury while upregulating AQP1 mRNA and protein expression [40] CLP rats Emodin pre-treatment significantly increased AQP1 mRNA and protein expression, suppressing sepsis-induced pulmonary apoptosis [26] LPS-exposed HPMECs Silencing HIF1A expression in LPS-induced cells attenuated AQP1 upregulation and regulated the cells' volume increase [41] AQP2 LPS-exposed rats Dexpanthenol increased AQP2 mRNA expression in kidney tissues through the SIRT1 signaling pathway [43] LPS-exposed rats Rhein treatment attenuated the downregulation of AQP2 protein expression in the kidneys [42] LPS-exposed rats Propofol pre-treatment protected the rats from further kidney complications by restoring AQP2 mRNA levels [44] AQP3 CLP rats Ss-31 treatment resulted in decreased protein expression of AQP3 and pulmonary vascular permeability [27] AQP4 LPS-exposed mice TGN-020 treatment resulted in downregulation of AQP4, suppression of inflammatory cytokine production, and better survival rates [75] AQP5 LPS-exposed mice Lipoxin A 4 presents a protective role in lung injury by upregulating AQP5 protein expression in lung tissue [47] LPS-exposed mice Fasudil upregulates AQP5 mRNA and protein levels while eliminating LPS-induced lung edema and preventing LPS-induced pulmonary inflammation [46] LPS-exposed mice Estradiol treatment pre-LPS exposure upregulated AQP5 mRNA and protein levels, reducing oxidative stress and inflammatory responses [36] LPS-exposed rats Hydrogen-rich saline reverses AQP5 mRNA and protein downregulation [38] LPS-exposed rats Pre-treatment with increasing concentrations of soy isoflavone resulted in dose-dependent upregulation of AQP5 mRNA and protein, alleviating pulmonary edema and lung damage [37] CLP rats…”
Section: Aquaporin Regulators In Experimental Models Of Sepsismentioning
confidence: 99%